LncRNA SNHG3 sponges miR‐577 to up‐regulate SMURF1 expression in prostate cancer - Li Teng; Yi Xing; Fan Yang; Yangyang Sun; Shaojin Zhang; Qingwei Wang; Weixing Zhang (2020)
Abstract Prostate cancer remains one of the most prevalent cancers and the main causes of cancer‐related deaths in males. Various articles introduced that long noncoding RNAs (lncRNAs) are found in vital functions in the development and progression of cancers. Although SNHG3 (small nucleolar RNA host gene 3) has been investigated in many cancers, now researches on the role and mechanism of SNHG3 in prostate cancer are lacked. In this work, SNHG3 exerted high expression in prostate cancer cell lines. Suppression of SNHG3 inhibited cell proliferation, migration, EMT (epithelial‐mesenchymal transition) process and promoted cell apoptosis. Additionally, it was found that SNHG3 could bind with miR‐577. Subsequently, SMURF1 (Smad ubiquitination regulatory factor 1) was identified as a downstream target of miR‐577 and had a negative correlation with miR‐577. SNHG3 was found to positively regulate SMURF1 expression. Furthermore, rescue assays demonstrated that co‐transfection of pcDNA3.1/SMURF1 reversed the effects of SNHG3 knockdown in cell proliferation, migration, EMT process and cell apoptosis. SNHG3 also promoted tumorigenesis in vivo. All the results above explained that SNHG3 accelerated prostate cancer progression by sponging miR‐577 to up‐regulate SMURF1 expression, suggesting that SNHG3 may act as a biomarker for prostate cancer patients.